PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMAHAMAN AKUNTANSI, PENERAPAN SAP, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Bu - Nilam Sari; Amir Hasan; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to determine the effect: human resource capacity, understanding of accounting, appliance of public accounting standard toward, utilization of information technologi, and the goverment internal control system to the quality of local goverment financial statement. It is using purpose sampling metho, the popullation in the study is servants in Bungo region. Namely the head of department, the financial officer, and treasurer/financial staff. the sample and the researce are 70 respondents who meet the criteria. The data collection technique user questionnaire. And the data analysis user multiple linear regression by SPSS. The research indicates that: human resource capacity has a positive significant effect on the quality of local goverment financial statement, where the significant value are 0,000<0,05. Understanding of accounting has a negative significant effect on the quality of local goverment financial statement, where the significant value are 0,040<0,05. Application of public accounting standard has not a significant effect on the quality of local goverment financial, where the significant value are 0,236<0,05. utilization of information technologi has a positive significant effect on the quality of local goverment financial statement, where the significant value are 0,022<0,05. And the goverment accounting intern control has a positive significant effect on the quality of local goverment financial statement where the significant value are 0,000<0,05.Keywords : financial statement, human resource, accounting, information techologi, and internal control system.